DETERMINING INITIAL ASSIGNMENT FOR SOLVING QUADRATIC ASSIGNMENT PROBLEMS - Elly Rosmaini (Proceedings of ICMSA, 2005)
The Quadratic Assignment Problem is a combinatorial problem ofdeciding the placement of facilities in specified locatians in such a waythat will to minimize an objective function expressed in terms ofdistance each location and flows each facilities. First they a simpleheuristic approach is used to obtain an initial assignment point..Hetristic Tabu search method is the implemented in other to getanother assignment point, which in tum will be used as a starting pointfor Nonlinier Programing approach. The continuous result of nonlinierprograming problem are the prosesed using another heuristic method toobtain an integer feasible solution to the quadratic assignment problem.The non convex behavior of the problem suggests that a good startingis necessary in order to obtain global solution. The procedure is thenimplemented on Backboard Wiring problem with dimension 20 x 20.Keywords; Quadratic Assignment problems; Tabu Search.